2017
DOI: 10.1093/ejcts/ezx207
|View full text |Cite
|
Sign up to set email alerts
|

The identification of sub-centimetre nodules by near-infrared fluorescence thoracoscopic systems in pulmonary resection surgeries

Abstract: NCT02611245.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…These results with an ICG dose of 5 mg/kg and imaging 24 hours after infusion have recently been replicated by Mao et al In their study, NIR imaging with second window ICG identified 68 of 76 nodules in 36 patients. All nodules not detected with imaging were at least 1.3 cm deep to the pleural surface.…”
Section: Clinical Applicationsmentioning
confidence: 60%
“…These results with an ICG dose of 5 mg/kg and imaging 24 hours after infusion have recently been replicated by Mao et al In their study, NIR imaging with second window ICG identified 68 of 76 nodules in 36 patients. All nodules not detected with imaging were at least 1.3 cm deep to the pleural surface.…”
Section: Clinical Applicationsmentioning
confidence: 60%
“…Okusanya et al injected ICG (5 mg/kg) intravenously 24 h before surgery, the nodule detection rate was 88.9% [16/18], the NIRF imaging also identified five additional sub-cm nodules, three metastatic adenocarcinomas and two metastatic sarcomas (6). Mao et al showed that the mean near-infrared signal to background ratio of the pulmonary nodules by intravenous ICG (5 mg/kg) was 3.29±1.81, the sensitivity and positive predictive value of ICG NIRF imaging were 88.7% and 92.6%, respectively (7). The sensitivity of this method is not affected by factors such as nodules size, metabolic activity, histological type, etc., and small nodules that are neglected by CT can be also visualized; however, this technique has limitations on the depth of nodules, which is reported in the literature as 1.3-2.0 cm (4,6).…”
Section: Pulmonary Nodule Localizationmentioning
confidence: 98%
“…Several kinds of molecules have been used to detect tumors intraoperatively. Indocyanine green (ICG) is one of the most widely used agents to detect many kinds of malignancies, including NSCLCs, together with near-infrared (NIR) fluorescence imaging (11,12). Although ICG is not a tumor-specific fluorescence dye, it accumulates in certain types of tumors because of the enhanced permeability and retention effect (13).…”
mentioning
confidence: 99%
“…Although ICG is not a tumor-specific fluorescence dye, it accumulates in certain types of tumors because of the enhanced permeability and retention effect (13). Intraoperative molecular imaging using ICG is reportedly able to detect small tumors in the lung (12,14); however, hyperplastic or inflammatory nodules may cause false-positive results (12) and ICG cannot distinguish between the tumor itself and the inflamed tissue around the tumor (11). Another potentially useful agent is the folate receptor (FR) targeted NIR tracer (OTL0038) that targets the FR-alpha that is expressed in 90% of pulmonary adenocarcinomas and 70% of squamous cell carcinomas (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation